3D Helix Engineering in Chiral Photonic Materials. Issue 33 (27th June 2019) - Kragt, Augustinus J. J.; Hoekstra, Davey C.; Stallinga, Sjoerd; Broer, Dirk J.; Schenning, Albertus P. H. J.
Abstract: Engineering the helical structure of chiral photonic materials in three dimensions remains a challenge. 3D helix engineered photonic materials are fabricated by local stratification in a photopolymerizable chiral nematic liquid crystal. The obtained chiral photonic materials reflect both handedness of circular polarized light and show super‐reflectivity. Simulations match the experimentally observed photonic properties and reveal a distorted helical structure. 3D engineered polymer films can be made that reflect both left‐ and right handed circular and linear polarized light dependent and exhibit a changing color contrast upon altering the polarization of incident light. Hence, these 3D engineered photonic materials are of interest for new and emerging applications ranging from anti‐counterfeit labels and data encryption to aesthetics and super‐reflective films. Abstract : 3D engineered photonic materials are of interest for emerging applications, such as anticounterfeit labels, data encryption, and super‐reflective films. 3D engineered chiral nematic‐liquid‐crystal materials, which exhibit a changing color contrast between the image and the surroundings upon changes in the polarization of incident light, are reported.